2015
DOI: 10.1002/bit.25897
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance evaluation of conventional and two‐phase hydrophobic stirred tank reactors for methane abatement: Mass transfer and biological considerations

Abstract: This study demonstrated for the first time the capability of methanotrophs to grow inside silicone oil (SO200) and identified the optimum cultivation conditions for enrichment of hydrophobic methanotrophs (high dilution rates (D) and low CH4 transfer rates). The potential of the hydrophobic methanotrophs enriched was assessed in a single-phase stirred tank reactor (1P-STR) and in a two-phase stirred tank reactor (2P-STR). Different operational conditions were systematically evaluated in both reactors (SO200 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Supplementary Material). The fact that the higher CH4 concentration gradient mediated by the increase in inlet CH4 concentrations supported higher ECs in both bioreactors confirmed that process operation was limited by CH4 mass transfer regardless the Mg 2+ concentration tested 32 . Moreover, biomass concentrations did not show significant differences among the three Mg 2+ concentrations tested in R1 (TSS concentrations of 1.2 ± 0.3, 1.7 ± 0.3, 1.7 ± 0.2 g L -1 in C1, C2 and C3, respectively) and R2 (TSS concentration of 1.3 ± 0.2, 1.1 ± 0.5, 1.7 ± 0.3 g L -1 in C1, C2 and C3, respectively).…”
Section: Influence Of Mg 2+ Concentration On Eps Productionsupporting
confidence: 55%
“…Supplementary Material). The fact that the higher CH4 concentration gradient mediated by the increase in inlet CH4 concentrations supported higher ECs in both bioreactors confirmed that process operation was limited by CH4 mass transfer regardless the Mg 2+ concentration tested 32 . Moreover, biomass concentrations did not show significant differences among the three Mg 2+ concentrations tested in R1 (TSS concentrations of 1.2 ± 0.3, 1.7 ± 0.3, 1.7 ± 0.2 g L -1 in C1, C2 and C3, respectively) and R2 (TSS concentration of 1.3 ± 0.2, 1.1 ± 0.5, 1.7 ± 0.3 g L -1 in C1, C2 and C3, respectively).…”
Section: Influence Of Mg 2+ Concentration On Eps Productionsupporting
confidence: 55%
“…Hence, the CH 4 -ECs recorded at 600 rpm (CH 4 -ECs of 10.1 ± 1.1 g CH 4 m -3 h -1 at 3 % NaCl and 5.0 ± 1.0 g CH 4 m -3 h -1 at 6 % NaCl) were significantly lower than those achieved at 300 rpm ( Figure 5). Higher agitation rates often support a better mass transfer of methane from the gas to the microbial community, thus enhancing CH -EC (Estrada et al, 2014;Cantera et al 2015). However, higher agitation rates in our study promoted an unexpected cell disruption as a result of a high shear stress on M. alcaliphilum 20Z ( Figure S2).…”
Section: <Figure 5>mentioning
confidence: 60%
“…In the case of the experimental run 4 (6 % NaCl and 600 rpm) the accumulation of intra-cellular ectoine decreased by a factor of 1.5 (23.8 ± 1.1 mg ectoine (g biomass) -1 ) compared to the experimental runs at 6% NaCl and 300 rpm. Although higher agitation rates can enhance the mass transfer of methane from the emission to the aqueous microbial community (Cantera et al, 2015), they can also induce a pernicious cellular stress, which resulted in a severe damage of the Methylomicrobium alcaliphilum 20Z culture.…”
Section: < Figure 1>mentioning
confidence: 99%
“…Current biotechnological processes could be the best solution for methane abatement due to their cost-effectiveness and their low environmental impact; however the implementation of bio-reactors for CH4 treatment is still limited. This limitation is mainly based on the low water solubility of CH4, which hampers the transport of this GHG to the microbial community and increases the cost of CH4 treatment biotechnologies [1]. In this context, the development of a CH4 biorefinery based on using CH4-laden emissions as raw materials to bio-synthesize high added value products represents a cost-effective solution for the mitigation of this GHG [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%